Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1038/s41375-018-0179-9
|View full text |Cite
|
Sign up to set email alerts
|

Front-line imatinib treatment in children and adolescents with chronic myeloid leukemia: results from a phase III trial

Abstract: A total of 156 patients (age range 1.3-18.0 years, median 13.2 years; 91 (58.3%) male) with newly diagnosed CML (N = 146 chronic phase (CML-CP), N = 3 accelerated phase (CML-AP), N = 7 blastic phase (CML-BP)) received imatinib up-front (300, 400, 500 mg/m, respectively) within a prospective phase III trial. Therapy response, progression-free survival, causes of treatment failure, and side effects were analyzed in 148 children and adolescents with complete data. Event-free survival rate by 18 months for patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
121
0
8

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 92 publications
(139 citation statements)
references
References 61 publications
6
121
0
8
Order By: Relevance
“…Just a few studies have reported CML in very young patients. The rarity of CML in this age group hinders the establishment of specific risk criteria and protocols for handling the disease in pediatric patients . Despite a low Sokal score, our patient rapidly progressed to blast crisis.…”
Section: Discussionmentioning
confidence: 85%
“…Just a few studies have reported CML in very young patients. The rarity of CML in this age group hinders the establishment of specific risk criteria and protocols for handling the disease in pediatric patients . Despite a low Sokal score, our patient rapidly progressed to blast crisis.…”
Section: Discussionmentioning
confidence: 85%
“…The haematological findings of the total cohort are reported in Table . More details on CML and patients’ status at diagnosis, treatment applied and overall outcome have been reported elsewhere (Suttorp et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Several prognostic CML scoring systems in adults (e.g. Sokal, Hasford or EURO scores) consider thrombocytosis as an adverse risk factor (Pfirrmann et al , ) and thus the observation of a higher proportion of children with thrombocytosis matches well with other characteristics of CML, pointing to a more aggressive presentation of the disease when diagnosed in the first decades of life (Pemmaraju et al , ; Kalmanti et al , ; Gurrea Salas et al , ; Hijiya et al , ; Millot et al , ; Suttorp et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the need for life‐long therapy with TKI and the known and unknown late effects of TKI may make SCT an attractive option for some. Therefore, there remains controversy regarding the role of SCT in pediatric patients with CML‐CP responsive to their first TKI therapy …”
Section: Management Of CML In Children and Adolescentsmentioning
confidence: 99%
“…Although SCT can be curative, there remains the risk of substantial transplant‐related morbidity and mortality, including infertility and long‐term complications, and the risk of later relapse . With recent advances surrounding SCT, children undergoing transplant have fewer complications and better outcomes compared to those of adults and hence SCT may be an option for patients who cannot or do not want to continue lifelong TKI therapy …”
Section: Management Of CML In Children and Adolescentsmentioning
confidence: 99%